FORMULATION DEVELOPMENT AND EVALUATION OF FAST DISSOLVING TABLET FOR TREATMENT OF HYPERTENSION - Ms. Pallavi B. Gholap1*, Dr. Kiran C. Mahajan2, Dr. Sunil J. Aher3, Mrs. Vrushali V. Neve4, Mr. Pawan N. Karwa5, Ms. Vrushali M. Bhalchim6, Dr. Mrudangsinh M. Rathod7, (Chelonian Research Foundation, 2023)
Fast dissolving tablet emerged as an alternative to the conventional oral dosage forms to improve the patient compliance. As the two extreme end age group (pediatrics and geriatric) complain about the swallowing of conventional oral solid dosage forms. fast dissolving tablets are solid dosage form containing medicinal substances or active ingredients which disintegrates rapidly within a few seconds when placed up on tongue. In this article the Enalapril Maleate immediate release tablets were prepared using croscarmellose sodium, sodium starch glycolate and crospovidone as super disintegrant separately and by direct compression method. Enalapril Maleate is the maleate salt form of enalapril, a dicarbocyl containing peptide and angiotensin converting enzyme (ACE) inhibitor with antihypertensive activity. The prepared immediate release tablets were evaluated for various parameters like disintegration time, wetting time, drug content, in-vitro drug release study etc. From the result it was observed that among three super disintegrants used, crospovidone showed better result in disintegration time, in-vitro drug release. The formulation of F4 containing crospovidone showed better result in disintegration time 13 sec. and maximum in-vitro drug release of 98.64±1.217 at the end of 20 minutes. F4 formulation is most complies to marketed product so F4 formulation shows better result. Keywords: Fast dissolving tablet, Direct Compression, Super disintegrants, Mouth Dissolving, Fast dissolving tablet, Evaluation.